Integrating phytoremediation with biomass valorisation and critical element recovery: A UK contaminated land perspective. (December 2015) - Jiang, Ying; Lei, Mei; Duan, Lunbo; Longhurst, Philip
Abstract: In the UK, the widespread presence of elemental contaminants such as arsenic and nickel in contaminated sites and more widely release of platinum group metals into the biosphere are growing concerns. Phytoremediation has the potential to treat land contaminated with these elements at low cost. An integrated approach combining land remediation with post-process biomass to energy conversion and high value element recovery is proposed to enhance the financial viability of phytoremediation. An analytical review of plant species suitable for the phytoremediation of nickel, Arsenic and platinum group metals is reported. Additionally, a preliminary model is developed to assess the viability of the proposed approach. A feasibility appraisal using Monte Carlo simulation to analyse project risk suggests high biomass yield plant species can significantly increase the confidence of achieving financial return from the project. The order of financial return from recovering elements was found to be: Ni > Pt > As. Highlights: Integrating phytoremediation with energy and elemental recovery is proposed. Plants suitable for uptake of high value elements have been critically reviewed. Project feasibility and financial viability is assessed using a mathematical model. Biomass yield is critical for the success of remediation and high economic return. Order of financial return from recovering elements was found to be: Ni > Pt > As.